The Effect of Human Resource Quality and Work Motivation on The Performance of Employees at The Pegadungan Kali Deres West Jakarta - Rohendrawan Rohendrawan; Murdiyono Murdiyono; Warman Warman (Jurnal Syntax Transformation, 2025)
The objectives of this study are (1) to determine the influence of human resource quality; (2) work motivation on the performance of employees at the Pegadungan Kalideres sub-district office in West Jakarta. The data used in this study is primary data. The population in this study consists of 32 employees, and the sampling technique used is a census. The respondents in this study are 32 employees of the Pegadungan Kalideres Subdistrict Office in West Jakarta. The analysis methods used include classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The results of the regression analysis concluded that Human Resource Quality and Work Motivation, both individually (partially) and simultaneously (simultaneously), have a positive and significant effect on Employee Performance. Human Resource Quality has a partial effect of 33.17% on Employee Performance, while Work Motivation has a partial effect of 20.43% on Employee Performance. Both variables together have a simultaneous effect of 88.88% on Employee Performance.